1996
DOI: 10.1002/ana.410390405
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aerobic training on fitness and quality of life in multiple sclerosis

Abstract: Fifty-four multiple sclerosis (MS) patients were randomly assigned to exercise (EX) or nonexercise (NEX) groups. Before and after 15 weeks of aerobic training, aspects of fitness including maximal aerobic capacity (VO2max), isometric strength, body composition, and blood lipids were measured. Daily activities, mood, fatigue, and disease status were measured by the Profile of Mood States (POMS), Sickness Impact Profile (SIP), Fatigue Severity Scale (FSS), and neurological examination. Training consisted of 3 x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
457
2
17

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 657 publications
(505 citation statements)
references
References 28 publications
29
457
2
17
Order By: Relevance
“…Structured group activity offers the advantage of a controlled dose-response setting for physical activity but may sacrifice the opportunity for individualized physical activity programs, which are recommended for people with MS. 23 However, individuals with varying levels of disability may gain psychological and social benefits from participation in group classes. For example, Petajan et al 5 attributed the 97% adherence rate in their study involving a group aerobic training program to social support. Similarly, Howe and Gomperts 23 reported that study participants motivated and supported each other during training.…”
Section: Type Of Physical Activitymentioning
confidence: 99%
“…Structured group activity offers the advantage of a controlled dose-response setting for physical activity but may sacrifice the opportunity for individualized physical activity programs, which are recommended for people with MS. 23 However, individuals with varying levels of disability may gain psychological and social benefits from participation in group classes. For example, Petajan et al 5 attributed the 97% adherence rate in their study involving a group aerobic training program to social support. Similarly, Howe and Gomperts 23 reported that study participants motivated and supported each other during training.…”
Section: Type Of Physical Activitymentioning
confidence: 99%
“…[55] The effect of exercise on MDD has been studied in healthy adults, persons with psychiatric conditions, and older adults. [56] Across studies, exercise appears to be more beneficial than no treatment, and in some studies it has been as effective as antidepressant medication and psychotherapy for mild to moderate depression.…”
Section: Exercisementioning
confidence: 99%
“…Each session consisted of 30 minutes of training on the elliptical trainer. This time period for this exercise intervention (15 sessions over 6 weeks) was within the range of time periods previously used for resistance and aerobic training in patients with MS [12,16,[35][36].…”
Section: Exercise Training Protocolmentioning
confidence: 92%